Preparing for the Worst Crisis Scenario on the Flag Carrier Garuda Indonesia in Digital Era - Aqida Nuril Salma (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2021)
Life in the digital era runs instant and fast-paced. The development of science and technology, especially the Internet and social media has a very strong influence. Not only does it affect the daily activities of people's lives, but also the activities of the professional world, especially in crisis communication that is considered more complex, and even raises new possibilities in which each company will be more vulnerable to crisis with a greater impact than ever. Thus, preparing for the worst possible scenario will help a crisis situation go as smoothly as possible. In consequence, organizations today are required to have a structured and internet-based crisis communication plan and policy as an effort to respond to these developments. This research paper presents an exploratory study conducted to understand how the practitioners prepare for the worst scenario and the strategy of handling it, and how the planning is influential to the success of crisis communication. An in-depth interview was conducted to senior corporate communication executives and crisis manager from High Reliability Organization (HRO). This paper concludes by suggesting and drawing up guidelines for practitioners to structuring an effective crisis communication plan as well as directions for future research in this domain for researchers to take up.